Feudal Echoes: Unveiling Gendered Power Through Indonesian Literary Narratives The Girl from the Coast By Pramoedya Ananta Toer - Tisna Andayani, Ni Putu; Candrayana, Ida Bagus (Proceeding Bali-Bhuwana Waskita: Global Art Creativity Conference, 2025)
This article analyzes Gadis Pantai (The Girl from the Coast) by Pramoedya Ananta Toer through a socialist feminist approach to uncover the forms of gender oppression embedded in the feudal social structure of early 20th-century in Java. Feudalism in The Girl from the Coast is portrayed as a system that freezes class and gender identity. It erases a woman's name, agency, and dignity in order to preserve the elite’s status quo. Bendoro positions the Girl from the Coast as a symbol of status rather than an equal partner. The Girl from the Coast serves as a vivid example of female resistance, even within constraints. Male dominance in the novel constructs a narrative that suppresses women's agency. The story illustrates how the institution of marriage can become a form of symbolic violence. Pramoedya gives voice to women who have long been silenced by social systems. The Girl from the Coast stands as a witness to how tradition can perpetuate subordination. Pramoedya not only critiques this feudal system, but also lays the foundation for reinterpreting the role of women within modern social structures. The protagonist, a young woman from a fishing community, is coerced into marriage with a Javanese aristocrat as a “trial wife,” reflecting the interwoven realities of patriarchy and class hierarchy. This study reveals that symbolic and social forms of violence depicted in the novel not only reinforce female subordination but also carve out space for symbolic resistance through the character’s emergence of self-awareness. By synthesizing feminist theory from Simone de Beauvoir and the patriarchy-class framework of Rosemarie Tong and Kate Millett, this article proposes that Gadis Pantai stands as an emancipatory narrative, remaining highly relevant for understanding gendered power relations in contemporary society.